Effect of Electrodes Separation in DC Plasma Sputtering on Morphology of Silver Coated Samples - Yahya, Khalid A; Rasheed, Ban F (Al-Nahrain Journal of Science, 2018)
In this work, the effect of the electrodes separation on plasma parameters and morphology properties for coated glass samples by silver metal using low voltage DC discharge plasma sputtering source. At fixed argon gas pressure 0.2 mbar and discharge currents Id(20,30,40,50 and 60)mA, for different electrodes separation d (3,4,4.5,5,6)cm was studied. The plasma sputtering source consists of a cylindrical chamber including two circular electrodes made from stainless steel. The cathode electrode is carrying the silver metal as a target and permanent magnet, while a glass sample coater is placed on the anode electrode. The plasma parameters: temperature of electron(Te) and ion density(ni) were determined by using cylindrical single Langmuir probe. Also, the surface morphology for the coater samples were studied by atomic force microscope (AFM). The results of this work shown that a linear increases in ions density and an exponential decreasing in electron temperature for different electrodes separation. Furthermore, the relationship between the average grain diameter and average grain height as a function of electrodes separation are nonlinear. The minimum average grain diameter is (90 nm) at d=4 cm for Id=40 mA and minimum average grain height is (5.5 nm) at the same electrodes separation and discharge current. When the temperature of electron increased, the values of average grain diameter increased while the values of average grain height decreased.